2023
DOI: 10.3389/fenvs.2023.1273564
|View full text |Cite
|
Sign up to set email alerts
|

Green finance pilot reform and corporate green innovation

Huaiming Wang,
Dongying Du,
Xiaojian Tang
et al.

Abstract: This study investigates the impact of the green finance pilot reform on corporate green innovation using the formation of the China Green Finance Pilot Reform in 2017 as a quasi-natural experiment. It shows that the green finance pilot reform increases corporate green innovation. Furthermore, by highlighting the differences between green enterprises and heavily polluting enterprises, it also shows that the positive relationship between the green finance pilot reform and corporate green innovation is more prono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Recommending research avenues based on the study's outcomes, while the present research predominantly focuses on green finance and financial institutions, future inquiries could delve into the correlation between green finance and green innovation (Wang et al, 2023). This study revealed a significant augmentation in green patent applications due to green finance, particularly evident in countries with poor environmental performance and those not part of the Comprehensive Regional Economic Partnership or the Belt and Road Initiative.…”
Section: Discussionmentioning
confidence: 84%
“…Recommending research avenues based on the study's outcomes, while the present research predominantly focuses on green finance and financial institutions, future inquiries could delve into the correlation between green finance and green innovation (Wang et al, 2023). This study revealed a significant augmentation in green patent applications due to green finance, particularly evident in countries with poor environmental performance and those not part of the Comprehensive Regional Economic Partnership or the Belt and Road Initiative.…”
Section: Discussionmentioning
confidence: 84%
“…For example, Han et al (2022) found that green finance can promote green innovation in heavy polluters. Wang et al (2023a) employed China's 2017 green finance reform pilot as a quasi-natural experiment, and found that the green finance pilot promotes green innovation. Based on the above analysis, Hypothesis 1a is proposed.…”
Section: H1: Green Finance Reduces Carbon Emission Intensitymentioning
confidence: 99%
“…Turning to enterprise factors, recent scholarship has delved into the role and impact of corporate involvement in environmental governance, employing both quantitative and qualitative methodologies (Liu, 2021;Wang et al, 2021). Some studies have specifically examined the influence of the green finance pilot reform on corporate green innovation, using the formation of the China Green Finance Pilot Reform as a case study (Wang et al, 2023). From a governmental perspective, research exploring the intricate relationship between environmental performance and environmental governance is ongoing.…”
Section: Introductionmentioning
confidence: 99%